PERAN ORGANIZATIONAL CITIZENSHIP BEHAVIOR DALAM MENGEMBANGKAN BUDAYA ORGANISASI GURU DI SMP SWASTA KECAMATAN PANONGAN - Amin Fitria Diningrum; Sri Utaminingsih; Imas Masriah (STKIP Pesisir Selatan, 2025)
This study aims to analyze the role of Organizational Citizenship Behavior (OCB) in developing teacher organizational culture in a private junior high school in Panongan District. Field phenomena indicate that teacher volunteer behavior strongly influences interaction patterns, work values, and habits that shape the school's organizational culture. The study used a qualitative approach with a case study design. Data were collected through in-depth interviews, participant observation, and documentation analysis, then analyzed using the Miles, Huberman, and Saldaña model. The results show that OCB contributes significantly to strengthening organizational culture through behaviors of altruism, courtesy, conscientiousness, civic virtue, and sportsmanship. Factors supporting the emergence of OCB include the principal's exemplary behavior, an open communication climate, and the school's religiosity. Obstacles that arise are related to teachers' administrative burdens, the dynamics of policy changes, and inconsistent role models at the managerial level. The study concludes that OCB is an important foundation in building a collaborative and sustainable teacher organizational culture.